Study on the synthesis of antibacterial plastic by using silver nanoparticles doped in zeolite framework - Le, Anh Quoc; Dang, Van Phu; Nguyen , Ngoc Duy; Nguyen Thi, Kim Lan; Vo Thi, Kim Lang; Nguyen , Quoc Hien (Nuclear Science and Technology, 2016)
Silver nanoparticles (AgNPs) doped in the zeolite framework (AgNPs/Z) were successfully synthesized by γ-irradiation in ethanol solution of silver ion-zeolite (Ag+/Z) prepared by ion exchange reaction between silver nitrate (AgNO3) and zeolite 4A. The effects of the Ag+ concentration and irradiation dose on the formation of AgNPs/Z were also investigated. AgNPs/Z with the silver content of about 10,000 ppm and the average particle size of AgNPs of about 27 nm was characterized by ultraviolet-visible spectroscopy, powder X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM). Firstly, AgNPs/Z was added into PP resins for creation of PP-AgNPs/Z masterbatch (Ag content of ~10.000 ppm) and then PP-AgNPs/Z plastics were preapared by mixing masterbatch with PP resins. The antibacterial activity of the PP-AgNPs/Z plastics was investigated against Gram-negative bacteria Escherichia coli (E. coli). The results showed that PP-AgNPs/Z plastic contained 100 ppm of Ag possessed a high antibacterial property, namely the bactericidal effect was more than 96 % on the platic surface. In conclusion, possessing many advantages such as: vigorously antibacterial effect and good dispersion in plastic matrix, AgNPs/Z is promising to be applied as bactericidal agent for plastic industry.